Hyperbaric oxygen therapy ameliorates osteonecrosis in patients by modulating inflammation and oxidative stress - Gerardo Bosco; Giuliano Vezzani; Simona Mrakic Sposta; Alex Rizzato; Garrett Enten; Abdullah Abou-samra; Sandro Malacrida; Silvia Quartesan; Alessandra Vezzoli; Enrico Camporesi (Taylor & Francis Group, 2018)
Early stages of avascular necrosis of the femoral head (AVNFH) can be conservatively treated with hyperbaric oxygen therapy (HBOT). This study investigated how HBOT modulates inflammatory markers and reactive oxygen species (ROS) in patients with AVNFH. Twenty-three male patients were treated with two cycles of HBOT, 30 sessions each with a 30 days break between cycles. Each session consisted of 90 minutes of 100% inspired oxygen at 2.5 absolute atmospheres of pressure. Plasma levels of tumor necrosis factor alfa (TNF-α), interleukin 6 (IL-6), interleukin 1 beta (IL-1β) and ROS production were measured before treatment (T0), after 15 and 30 HBOT sessions (T1 and T2), after the 30-day break (T3), and after 60 sessions (T4). Results showed a significant reduction in TNF-α and IL-6 plasma levels over time. This decrease in inflammatory markers mirrored observed reductions in bone marrow edema and reductions in patient self-reported pain.